Rugrats: space invaders! - Albee, Sarah (New York : Simon spotlight / Nickelodeon, 1998)
The Rugrats babies become convinced that Earth is about to be invaded by space aliens.
Keywords: Babies -- Fiction; Extra-terrestrial beings -- Fiction